학업을 병행하는 임상치과위생사의 직무만족도 영향 요인 - 민희홍; Hee-hong Min; 최미현; Mi-hyun Choi; 윤미혜; Mi-hae Yun (Han'guk Ch'iwisaeng Hakhoe chi, 2019)
Objectives: This study was conducted to understand the influencing factors of job satisfaction of clinical dental hygienists in schoolwork, and use the basic data to enhance their job satisfaction. Methods: A self-reported questionnaire was filled out by 210 dental clinic hygienists from June 10 to August 30 of 2018. Data were analyzed using SPSS 22.0. Independent t-test, one-way ANOVA, Scheffe’s post-hoc test, and Pearson correlation coefficient were reviewed, and a multiple regression analysis was conducted. Results: The scores of subjects' professional self-concept, self-esteem, job stress, and job satisfaction were 3.37, 3.80, 2.79, and 3.37, respectively. The influencing factors of job satisfaction of clinical dental hygienists in schoolwork included marital status, support in workplace, professional self-concept, and job stress, with 41.6% of the explanatory power. Conclusions: The stronger the professional self-concept, the lower the job-stress and higher the job satisfaction. The job satisfaction was also higher in the group in which the subjects were married and getting support in the workplace compared to the other group with no support in the workplace. Therefore, support systems and institutional support are required for clinical dental hygienists to be continuously educated in the workplace.